Solute transport in variably saturated flow in porous media with dual porosity - Lorentz, Simon A., author; McWhorter, David B., advisor; Ward, Robert C., committee member; Sanders, Thomas G., committee member (Colorado State University. Libraries, 1986)
The transport of chemicals through solid waste disposal piles presents a potential source of surface and groundwater contamination. In an effort to determine the scope of the potential hazard, many laboratory tests have been devised and used on the waste materials. A prerequisite for such a test would be that it yield reproducible results. An added advantage, however, would be that the mechanisms of leachate generation in the test have some resemblance to those in the field. Therefore, on the premise that hydrodynamic conditions and solid-to-liquid ratios have a significant influence on the rate and quantities of chemical leached in situ, a standardized column leach test was developed for laboratory evaluation of oil shale solid wastes (Nazareth, 1984). In addition, an analytical model was developed to describe the effluent breakthrough curve (BTC). The physical mechanisms modelled were convection, dispersion and linear equilibrium adsorption in a partially saturated porous medium. The model predicted the results of leach tests on fine grained oil shale waste material. However, tests on large grained materials produced BTCs of a conservative chemical which were extremely asymmetric and exhibited and excessive tailing effect. This phenomenon could be caused by the diffusion of solute out of the retorted oil shale particles into the mobile water phase. The need for a model which included this additional process was realized. An approximate model and a solution for these processes are developed in this study (Model 1). The solution is compared with another approximate model in which the diffusion process is ignored (Model 3). This comparison shows that, for a certain combination of the physical properties of the medium, the BTC can be predicted without considering the diffusion process even though the material has a significant intra-particle volume. Model 1 predictions are compared with experimental BTX: results from column leach tests. The columns are packed with selected spherical particles which have a large intra-particle volume. Different sizes of particles are used and advection rates are varied in these idealized tests. The model is also used to predict the results of BTCs resulting from tests on a retorted oil shale packed at different bulk densities. The model successfully predicts the BTCs of leach tests where the unsaturated flew in the medium can be modelled by a Green-Ampt type wetting front. In other materials the model can be used to predict the data by calibrating the dispersion coefficient. In addition it is shown that for a specific combination of test parameters the intra-particle diffusion mechanism may be neglected even though the material has a large intra-particle volume.
Keywords: Diffusion -- Mathematical models; Oil-shale industry -- Waste disposal; Leaching